The Phytochemistry, Pharmacology, and Quality Control of Tetrastigma hemsleyanum Diels & Gilg in China: A Review - Zhu, Ruyi; Xu, Xiaofen; Ying, Jialiang; Cao, Gang; Wu, Xin (Frontiers in Pharmacology, 2020)
Tetrastigma hemsleyanum Diels & Gilg (TDG), the family member of Vitaceae, is a traditional herbal medicine in China. The root of TDG can be immediately used after cleaning the muddy soil, and can be dehydrated for dry use. TDG is able to be collected all year round, which is commonly used in the treatment of hepatitis, infantile high fever, snake bite, etc. Based on phytochemistry, the chemical components of TDG are divided into flavonoids, phenolic acids, terpenes, steroids, polysaccharide and other compounds, showing many pharmacological effects which include anti-tumor, anti-oxidation, anti-inflammatory, antipyretic, analgesic and immunomodulatory activity, as well as other activities. Currently, TDG involves some problems of the reduction of wild resources, the backward processing methods, and storage difficulties as well as the imperfection of detection methods. Therefore, this review summarizes the literature of the past 20 years, and the purpose of this review is to summarize the recent researches on the phytochemistry, pharmacology, quality control and clinical application of TDG. The above discussions provide new insights for the future research on TDG.